From Pan-Africanism to African regionalism: A chronicle. Issue 1 (2nd January 2020) - Aniche, Ernest Toochi
ABSTRACT: Classical African regionalism, as rooted in pan-Africanism, is a strategy for decolonisation, anti-colonial and neo-colonial struggles, and continental unity. Modern African regionalism is a means to achieving continental unity, collective self-reliance and economic transformation as well as to creating an agenda for solving African developmental challenges. The main objective of this paper, therefore, is to examine the historical evolution of pan-Africanism and regionalism in Africa from colonial to post-colonial era in order to trace the interface between them. The paper assesses the extent to which regional integration in Africa has been able to achieve its stated objectives and targets over the years. It also investigates the various obstacles, constraints and challenges that militate against the accomplishment of its objectives, opportunities and prospects. It then interrogates the narratives of the Western neoliberal theories of integration or approaches to African integration. Subsequently the paper suggests that there is a need to deconstruct them in the search for paradigm shift in African integration. It contends that there is also a need to evolve a new theoretical approach to African integration anchored on neo-neo-integrationism of post-neo-functionalism or post-modern integrationism of post-neo-nationalism.